CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. SIDO MUNCUL TBK - Novita Damayanti; Muminto Arief; Syifa Rachmawati (Jurnal Pustaka Komunikasi, 2018)
CSR activities are the company's contribution to society by balancing attention to economic, social, and environmental aspects as one of the determinants of good reputation. Research wants to know how the implementation and categorization of PT Sido Muncul CSR in maintaining reputation. The concept used is the Triple Bottom Line and the Theory of Excellence in Public Relations. The Triple Bottom Line concept to explain companies that want to be sustainable and guarantee the company's business continuity must pay attention to the concept of 3P (profit, people, planet). Excellence in public relations, to identify the communication model that PR is implementing in carrying out its role or function for the organization or company. The research approach to research is qualitative with the method used is a case study. The results of the research obtained are in every CSR program activity that is routinely carried out by PT. Sido Muncul practices a two way asymmetrical model because PR implements unbalanced two-way communication, where companies and communities do not attempt to adapt themselves to common interests, to change the public to fit the goals or objectives of the organization.